The legality of wasiyyah wajibah in achieving maqasid al-shariah - Md. Habibur, Rahman; Abu Talib, Mohammad Monawer (2020)
Wasiyyah wajibah is an obligatory will, prescribed in some jurisdictions for the sake of gra ndchildren whose father dies during the lifetime of their grandfather. Maqasid al-shariah refer to the underlying objectives of Islamic rulings, which are summarized as the protection of faith, life, lineage, intellect and wealth.They are further described as the well-being(maslahah) of mankind which is portrayed as achieving the benefit a nd repulsing the harm. This study intends to analyse the lawfulness of wasiyyah wajibah in the context of maqasid a l-shariah. The study is qualitative in nature and a method of content analysis is used to conduct this study. Though wasiyyah is voluntary in nature, this form of wasiyyah is made obligatory to ensure social solidarity for the deprived grandchildren and social equality in distributing the inheritance of their grandfather among his inheritors. The study concludes that the lawfulness of wasiyyah wajibah goes in line with maqasid al-shariah as it protects the lives of underprivileged grandchildren and repulses the hardship of poverty and economic discrimination f rom their lif e. Thus, it ensures the well-being of those deprived grandchildren in particular, and achieves social justice and social solidarity in Islamic inheritance at large.